2020
DOI: 10.3389/fendo.2020.573891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Non-insulin Anti-hyperglycemic Agents on Gut Microbiota: A Systematic Review on Human and Animal Studies

Abstract: Background: As growing evidence links gut microbiota with the therapeutic efficacy and side effects of anti-hyperglycemic drugs, this article aims to provide a systematic review of the reciprocal interactions between anti-hyperglycemic drugs and gut microbiota taxa, which underlie the effect of the gut microbiome on diabetic control via bug-host interactions. Method: We followed the PRISMA requirements to perform a systematic review on human vs. animal gut microbiota data in PubMed, SCOPUS, and EMBASE database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 92 publications
(350 reference statements)
1
29
0
2
Order By: Relevance
“…Another strength of our study is to use self-reported measures that are validated for Polish conditions, such as the FFQ to assess dietary factors, and then to use those measures in statistical analysis. Apart from diet, there are many other factors influencing our microbiome, such as the mode of delivery (vaginal or caesarean), the mode of feeding in early infancy (breastfeeding vs. formula), exposure to viral or bacterial antigens, treatment with antibiotics and several other groups of pharmacotherapeutics, genetic predispositions, age, and environmental factors such as air pollution, exercise, or stress [ 44 , 48 , 49 , 51 , 73 , 74 ]. The factors that may influence the microbiota changes in the course of our study are included in our original questionnaires: the SQ at the beginning of the protocol and in the follow-up visit and the MQ in the monitoring process included at the V2 visit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another strength of our study is to use self-reported measures that are validated for Polish conditions, such as the FFQ to assess dietary factors, and then to use those measures in statistical analysis. Apart from diet, there are many other factors influencing our microbiome, such as the mode of delivery (vaginal or caesarean), the mode of feeding in early infancy (breastfeeding vs. formula), exposure to viral or bacterial antigens, treatment with antibiotics and several other groups of pharmacotherapeutics, genetic predispositions, age, and environmental factors such as air pollution, exercise, or stress [ 44 , 48 , 49 , 51 , 73 , 74 ]. The factors that may influence the microbiota changes in the course of our study are included in our original questionnaires: the SQ at the beginning of the protocol and in the follow-up visit and the MQ in the monitoring process included at the V2 visit.…”
Section: Discussionmentioning
confidence: 99%
“…Study Questionnaire (SQ) has been constructed to collect basic information concerning sociodemographic and health-related data. The participants will provide information on personally identifying data, as well as known factors influencing microbiota composition and function: diet, smoking cigarettes, physical activity, overall health status and specific somatic diseases connected with dysbiosis, and the use of dietary supplements and medications known to influence microbiota to a large extent, e.g., antibiotics, proton-pump inhibitors (PPIs), metformin, laxatives, systemic steroids or nonsteroidal anti-inflammatory drugs (NSAIDs) or antipsychotics additionally known to induce both metabolic and inflammation alteration [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. Both SQ and MQ applied every 2 weeks are based on exclusion criteria ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Another strength of our study is to use self-reported and validated for polish conditions FFQ to assess dietary factor and then use it in statistical analysis. Apart from diet, there are many other factors influencing our microbiome such as the mode of delivery (vaginal or caesarean), the mode of feeding in the early infancy (breastfeeding vs. formula), exposure to viral or bacterial antigens, treatment with antibiotics and several other groups of pharmacotherapeutics, genetic predispositions, age, environmental factors such as air pollution, exercise or stress [55][56][57][58][59][60]. The factors that may influence the microbiota changes in the course of our study are included in our original questionnaires: SQ at the beginning of the protocol and in the follow-up visit and MQ in the monitoring process including V2 visit.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is worth remembering that there are many factors impacting microbiota function and composition, e.g., the diet, [ 39 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 ] and they should be assessed along the study process.…”
Section: Practical Applicationsmentioning
confidence: 99%